Role of macrophages in serum colony-stimulating factor induction by Lactobacillus casei in mice. - Nanno, M (1988)
Heat-killed Lactobacillus casei YIT9018 (LC9018), when injected intravenously into mice at a dose of 4 to 40 mg/kg, induced the production of serum colony-stimulating factor (CSF). Since this induction was observed in both C3H/HeJ and C3H/HeN mice, LC9018 was considered to act differently from lipopolysaccharide. The amount of serum CSF induced by LC9018 in nude mice and whole-body-X-ray-irradiated mice was similar to that in control mice, but the induction of serum CSF was suppressed by the previous administration of carrageenan, indicating that macrophages, but not T cells, were responsible for serum CSF induction by LC9018. To determine whether macrophages themselves produce CSF or help other cells produce CSF in response to LC9018, we prepared adherent cells from the peritoneal cavity of normal mice and examined CSF activity in their conditioned media. Peritoneal adherent cells did not produce CSF without LC9018, but when cultivated with 1 mg of LC9018 per ml, they produced CSF at the same time that serum CSF was induced after the intravenous administration of LC9018. Additionally, in vitro-induced CSF formed macrophage, granulocyte, and mixed colonies, as serum CSF did. CSF production by peritoneal adherent cells was completely inhibited by cycloheximide (50 micrograms/ml), and neither the elimination of T cells from the peritoneal adherent cells by treating them with anti-Thy-1.2 antibody plus complement nor the addition of T cells affected CSF production. These results suggest that heat-killed LC9018 induces serum CSF in mice via direct stimulation of macrophages to produce CSF de novo.